Improved average consensus algorithm based distributed cost optimization for loading shedding of autonomous microgrids. (December 2015) - Liu, Wei; Gu, Wei; Xu, Yinliang; Xue, Shuai; Chen, Ming; Zhao, Bo; Fan, Miao
Highlights: A two-layer improved average consensus algorithm (IACA) is proposed. IACA based distributed global information sharing is proposed. IACA based distributed cost optimization (DCO) considering cost is proposed. Abstract: This paper addresses a new distributed cost optimization (DCO) method for load shedding (LS) of an islanded microgrid considering cost. A two-layer improved average consensus algorithm (IACA) of multi-agent system (MAS) is proposed, and the consensus characteristic of which is analyzed in detail. With the global information discovered in the first layer of the IACA, the DCO of LS can be solved by using the synchronization processing of the IACA in the second layer. PSCAD/EMTDC-based simulation models are built to study the value settings of consensus constants and the performances of the proposed DCO method. Simulation results verified the convergence improvement of the IACA and the effectiveness of the proposed DCO.